Crystal structure of the plant receptor-like kinase TDR in complex with the TDIF peptide - Morita, Junko; Kato, Kazuki; Nakane, Takanori; Kondo, Yuki; Fukuda, Hiroo; Nishimasu, Hiroshi; Ishitani, Ryuichiro; Nureki, Osamu (Nature communications, 2016)
In plants, leucine-rich repeat receptor-like kinases (LRR-RKs) perceive ligands, including peptides and small molecules, to regulate various physiological processes. TDIF, a member of the CLE peptide family, specifically interacts with the LRR-RK TDR to inhibit meristem differentiation into tracheary elements, and promotes cell proliferation. Here we report the crystal structure of the extracellular domain of TDR in complex with the TDIF peptide. The extracellular domain of TDR adopts a superhelical structure comprising 22 LRRs, and specifically recognizes TDIF by its inner concave surface. Together with our biochemical and sequence analyses, our structure reveals a conserved TDIF-recognition mechanism of TDR among plant species. Furthermore, a structural comparison of TDR with other plant LRR-RKs suggested the activation mechanism of TDR by TDIF. The structure of this CLE peptide receptor provides insights into the recognition mechanism of the CLE family peptides. The TDF peptide interacts with the leucine-rich repeat receptor-like kinase TDR to regulate meristem differentiation in plants. Here, the authors solve the structure of the extracellular domain of TDR in complex with TDIF and propose a mechanism for TDIF recognition.